Sir Thomas Phillipps collection - Phillipps, Thomas, Sir, 1792-1872; Cooper, John Gilbert, 1723-1769.
Manuscript materials formerly a part of Sir Thomas Phillipps' collection relating chiefly to various aspects of the colonial history of North America and the West Indies. Of particular note are papers relating to the Board of Trade and Sir William Blathwayt; letterbooks of George Macartney while Governor of the Caribbean Islands; English and Italian genealogical material; papers of Jean Louis Berlandier relating to his surveys of the U.S.-Mexican border and to his various explorations in Mexico, Lower California, and Texas; English court records and reports; and miscellaneous papers of various colonies in British North America.
Microfilm edition available, in part
Microfilm produced from originals in the Manuscript Division.
Microfilm of original letters of John Gilbert Cooper in the Bodleian Library, Oxford University (Oxford, England).
Great Britain: Bodleian Library, Oxford University, Oxford
English antiquarian and bibliographer.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Berlandier, Jean Louis, -- -1851.; Blathwayt, William, -- 1649?-1717.; Macartney, George Macartney, -- Earl, -- 1737-1806.; Courts -- Great Britain; Baja California (Mexico : Peninsula) -- Discovery and exploration; Caribbean Area -- History; Great Britain -- Colonies -- America; Great Britain -- Genealogy; Italy -- Genealogy; Mexico -- Boundaries; Mexico -- Boundaries -- United States; Mexico -- Discovery and exploration; Mexico -- Surveys; Texas -- Discovery and exploration; United States -- Boundaries; United States -- Boundaries -- Mexico; Antiquarians; Bibliographers